2022
DOI: 10.1055/a-1793-9232
|View full text |Cite
|
Sign up to set email alerts
|

Snare devices with thinner loop wire may provide higher performance for cold snare polypectomy in an experimental model

Abstract: Background and study aims Snare devices play an important role in treatment of intestinal polyps. However, there are no objective measurements for the characteristics of the various types of snare devices. Materials and methods Seven types of snare devices from four manufacturers were evaluated based on original measurements. The evaluated factors were stiffness, cutting quality, and change in force required for cutting depending on sheath shape. The latter two factors were evaluated by measuring the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…showed that when performing CSP on colorectal polyps measuring 3–7 mm, a snare with a thin 0.30 mm wire showed higher CRR than a thicker 0.42 mm wire. In an experimental model, the thinness of the loop wire and diameter of the snare positively correlated with the force at the time of lesion excision, but not with the stiffness of the loop or the characteristics of the snare device 22 . Contrarily, an international multicenter RCT that compared the efficacy of thin wire snares (0.30 mm) versus thick wire snares (0.47 mm) for colorectal polyps smaller than 10 mm found no statistically significant difference in the IRR between both groups 23 .…”
Section: Exemplary Procedures Of Cspmentioning
confidence: 87%
See 1 more Smart Citation
“…showed that when performing CSP on colorectal polyps measuring 3–7 mm, a snare with a thin 0.30 mm wire showed higher CRR than a thicker 0.42 mm wire. In an experimental model, the thinness of the loop wire and diameter of the snare positively correlated with the force at the time of lesion excision, but not with the stiffness of the loop or the characteristics of the snare device 22 . Contrarily, an international multicenter RCT that compared the efficacy of thin wire snares (0.30 mm) versus thick wire snares (0.47 mm) for colorectal polyps smaller than 10 mm found no statistically significant difference in the IRR between both groups 23 .…”
Section: Exemplary Procedures Of Cspmentioning
confidence: 87%
“…In an experimental model, the thinness of the loop wire and diameter of the snare positively correlated with the force at the time of lesion excision, but not with the stiffness of the loop or the characteristics of the snare device. 22 Contrarily, an international multicenter RCT that compared the efficacy of thin wire snares (0.30 mm) versus thick wire snares (0.47 mm) for colorectal polyps smaller than 10 mm found no statistically significant difference in the IRR between both groups. 23 The report concluded that standardization of the operator's skill level was more important than snare performance.…”
Section: Selection Of Snare Productsmentioning
confidence: 99%
“…1,2,14,15 However, no model can accurately and objectively evaluate and compare the resection ability of these snares, and only preliminary resection evaluations using substitutes, such as gelatin, have been conducted. 16 Since differences in resection targets will alter the results of resection ability evaluation, the human colonic mucosa should be used as the resection target to accurately evaluate snare resection ability. However, it is difficult to procure sufficient human colonic mucosa for evaluation.…”
Section: Introductionmentioning
confidence: 99%